DETERMINATION OF SERUM GONADOTROPIN BIOLOGICAL ACTIVITY BY ENZYME-LINKED IMMUNOSORBENT ASSAY - Yerkekulova, K.K.; Turaliyeva, M.A.; Alibayev, N.; Yermekbayeva, A.; Alikhanov, O.; Beketauov, O. (Eurasian Journal of Applied Biotechnology, 2025)
In this paper, a comparative study of various methods for determining the activity of a biological product based on blood serum of mare in foal (BSMF) is carried out. The relevance of the study is due to the need for accurate and reliable quality control of biological products used in veterinary medicine and reproductive biotechnology. In the course of the work, a method was developed based on enzyme-linked immunosorbent assay (ELISA) that allows determining the activity of a biological product based on the content of follicle-stimulating hormone (FSH). The study showed that performing the analysis on a 2 ml sample from each batch of serum ensures representativeness and reproducibility of the results. The activity of the biological product is determined based on the FSH content, and it was found that the FSH concentration in the range of 4-4.9 mIU/ml corresponds to an activity of 120 mU. With an increase in the FSH concentration by 1 mIU/ml, the activity of the biological product increases by 20 mU. The proposed method has high sensitivity and specificity, which ensures reliable quantitative determination of the activity of the biological product. The implementation of this method will improve the quality of control and standardization of batches of blood serum of mare in foal, which is important for ensuring the stability and effectiveness of the biological product in clinical practice. The results obtained are of practical importance for enterprises engaged in the production and quality control of biologically active drugs.